2010
DOI: 10.4103/1596-3519.68360
|View full text |Cite
|
Sign up to set email alerts
|

Social consequences of epilepsy: A study of 231 Nigerian patients

Abstract: Social difficulties are common among epileptics. Effort should be made to educate the society about epilepsy, and physicians treating patients with epilepsy should aim at achieving a good seizure control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 16 publications
6
19
0
1
Order By: Relevance
“…PWE have a higher risk than the general population of suffering depression, not just after but also before the onset of epilepsy. [30,31] The prevalence of depressive and anxiety symptoms of 25% each in this study is similar to findings by Allgower et al [32] Inability to find (or loss of) job as a result of epilepsy [17] and the attendant failure to meet role obligations expected of an adult may be contributory factors to the development of emotional distress in our subjects. Although there are more males among our subjects, the females had higher percentages of depressive and anxiety symptoms.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…PWE have a higher risk than the general population of suffering depression, not just after but also before the onset of epilepsy. [30,31] The prevalence of depressive and anxiety symptoms of 25% each in this study is similar to findings by Allgower et al [32] Inability to find (or loss of) job as a result of epilepsy [17] and the attendant failure to meet role obligations expected of an adult may be contributory factors to the development of emotional distress in our subjects. Although there are more males among our subjects, the females had higher percentages of depressive and anxiety symptoms.…”
Section: Discussionsupporting
confidence: 88%
“…[6] In addition, PWE live constantly with the stress of a highly stigmatizing chronic illness. [17] The predictors of emotional distress in PWE include gender, duration of the disease, uncontrolled seizures, poly-pharmacy, felt stigma, [4,11,18,19] lack of social support, unemployment, and the attendant worrying. [20] The previous studies of epilepsy and emotional distress in Nigeria were conducted in the Southern part of the country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most common social problems a patient with epilepsy may experience is stigmatization and this was observed to be prevalent (one-third) in our study population, as was observed in previous studies (13,27). Stigma in epilepsy has been extensively studied (13,21,27) and is known to have several complications (13)(14)(15)(16). In the present study, stigma was associated with impairment in other psychosocial domains like finance and physical and occupational activities, thus supporting previous studies that have found stigma to be a risk factor for additional psychosocial problems (7,21).…”
Section: Psychosocial Problems Of Epilepsy Patientssupporting
confidence: 88%
“…common and are known to elevate the risk of psychopathology as well as that of the occurrence of the other complications of psychosocial dysfunctions described above (3,(13)(14)(15)(16)(17)(18)(19)(20)(21). Stigma is a psychosocial problem that occurs in patients with epilepsy globally and prevalence rates may be more than 50%.…”
Section: Introductionmentioning
confidence: 99%